2022
DOI: 10.1186/s12935-022-02732-6
|View full text |Cite
|
Sign up to set email alerts
|

Cirsiliol regulates mitophagy in colon cancer cells via STAT3 signaling

Abstract: Background Mitophagy is a type of selective autophagy for dysfunctional mitochondria and plays a key role in tumorigenesis and cancer progression. However, whether mitophagy plays a role in colon cancer remains unclear. Cirsiliol is a natural product and has been found to exert anti-cancer effects in multiple tumors. The effects of cirsiliol in the tumorigenesis and progression of colon cancer remain unknown. Methods CCK8 assay, plate cloning assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Cirsiliol is a flavonoid that has been reported to have therapeutic effects on esophageal squamous cell carcinoma, melanoma, non-small cell lung cancer and breast cancer [ 13 , 15 , 40 , 41 ]. It may affect mitochondrial function and ATP generation or target the appropriate protein to exert its inhibitory effects [ 14 , 42 ]. However, the mechanism of action of cirsiliol in OS is unknown, warranting further investigation, particularly in resistant cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cirsiliol is a flavonoid that has been reported to have therapeutic effects on esophageal squamous cell carcinoma, melanoma, non-small cell lung cancer and breast cancer [ 13 , 15 , 40 , 41 ]. It may affect mitochondrial function and ATP generation or target the appropriate protein to exert its inhibitory effects [ 14 , 42 ]. However, the mechanism of action of cirsiliol in OS is unknown, warranting further investigation, particularly in resistant cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that cirsiliol exerts multiple pharmacological effects, including anti-cancer, anti-inflammatory and anti-oxidative stress [ 10 13 ]. Although cirsiliol has been proven to be effective in treating esophageal squamous cell carcinoma and colon cancer [ 14 , 15 ], the effect and underlying molecular mechanisms of cirsiliol in OS remain elusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 a). Cirsiliol is an interesting compound regulator of mitophagy in cancer cells [103], apparently acting as an inhibitor of tyrosine kinase TYK2 (K D = 0.8 µM) in cancer cells and tumors [104]. Its anticancer effects have been well evidenced using different cell lines and tumor models in recent years [105,106].…”
Section: Ephedra Altissima Desfmentioning
confidence: 99%
“…In this situation, mitochondria can be cleaned by a process known as mitophagy, a kind of selective autophagy. Mitophagy has been shown to play a function in either promoting or restricting carcinogenesis (9)(10)(11)(12). Furthermore, many studies have revealed that mitophagy is involved in immune function regulation (13).…”
Section: Introductionmentioning
confidence: 99%